How do Adult Protective Statutes Relate to Older Americans Seeking Insurance Advice? - Campbell, Benjamin Steele; Kalenkoski, Charlene; Lauderdale, Mitzi (Archives of Business Research, 2023)
In the United States, no two states are completely alike in how they govern their citizenry or regulate commerce within their borders. These differences may be used to examine the effects of various laws by contrasting the differences in the way each state attempts to resolve a perceived problem and the resulting outcome. The following paper examines the relationship between consumer behavior and statutory solutions enacted to combat the problems of elder abuse, specifically financial exploitation. The statutory solutions are Adult Protective (AP) statutes. This paper focuses on AP statutes and their relationship to insurance advice seeking by older Americans. This paper finds that in under some circumstances insurance advice seeking behavior is related to the ways in which a state chooses to protect its elderly citizens from unscrupulous acts of persons or businesses. This article may serve as an opportunity for ethical professionals in financial services to understand how greater levels of regulation can result in opportunities for growth.